A Case of Coronavirus Disease 2019 With Concomitant Acute Cerebral Infarction and Deep Vein Thrombosis - Zhou, Bo; She, Jianqing; Wang, Yadan; Ma, Xiancang (Frontiers in Neurology, 2020)
We report a case of a 75-year-old woman diagnosed with severe coronavirus disease 2019 (COVID-19) complicated with acute cerebral infarction. The patient was admitted to our hospital on February 5th with severe COVID-19. Two weeks after admission, she was diagnosed with concomitant acute cerebral infarction via head computed tomography (CT) and deep vein thrombosis in both lower limbs. After symptomatic and supportive treatments, the patient was discharged on March 13th. She will comply with quarantine for another 2 weeks and receive rehabilitation training from a specialist doctor. Cerebral infarction should be considered and promptly managed in patients with COVID-19.